2013
DOI: 10.1152/japplphysiol.00064.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stabilizing or increasing respiratory motor outputs on obstructive sleep apnea

Abstract: To determine how the obstructive sleep apnea (OSA) patient's pathophysiological traits predict the success of the treatment aimed at stabilization or increase in respiratory motor outputs, we studied 26 newly diagnosed OSA patients [apnea-hypopnea index (AHI) 42 ± 5 events/h with 92% of apneas obstructive] who were treated with O2 supplementation, an isocapnic rebreathing system in which CO2 was added only during hyperpnea to prevent transient hypocapnia, and a continuous rebreathing system. We also measured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 77 publications
3
61
1
Order By: Relevance
“…In contrast to the findings of the current study and others, 30 Xie et al 31 reported that hyperoxia had no effect on mean AHI (room air vs. hyperoxia: 39 ± 6 vs. 34 ± 6 events/h, P = 0.25) and found there was no relationship between anatomy/collapsibility and the changes in AHI across participants. Apparent discrepancies are possibly explained by their greater average age (+10 y), more severe average collapsibility (Pcrit in the current study [ …”
Section: Altering Loop Gaincontrasting
confidence: 99%
“…In contrast to the findings of the current study and others, 30 Xie et al 31 reported that hyperoxia had no effect on mean AHI (room air vs. hyperoxia: 39 ± 6 vs. 34 ± 6 events/h, P = 0.25) and found there was no relationship between anatomy/collapsibility and the changes in AHI across participants. Apparent discrepancies are possibly explained by their greater average age (+10 y), more severe average collapsibility (Pcrit in the current study [ …”
Section: Altering Loop Gaincontrasting
confidence: 99%
“…In the category 2b patients, a primarily nonanatomic intervention may be beneficial. For example, oxygen therapy reduces loop gain and OSA severity by approximately 50% in patients with OSA with high loop gain (22), acetazolamide reduces loop gain and OSA severity by about 50% (21), and stabilizing or increasing CO 2 reduces OSA severity by more than 30% in patients with high loop gain (by controller gain) (47). A roughly doubling of genioglossus EMG activity reduces Pcrit by 1.6 cm H 2 O (48), whereas a standard dose of eszopiclone increases the arousal threshold and reduces OSA severity by approximately 45% in patients with OSA with a low arousal threshold (9).…”
Section: The Palm Scale Simplified Approaches and Potential Novel Tmentioning
confidence: 99%
“…These respiratory stimuli can activate the upper airway dilator muscles to restore pharyngeal patency during sleep, which can protect against OSA (5)(6)(7)(8)(9). However, restoration of sufficient airflow can only occur if ventilatory drive can build up during sleep without an arousal (5,10,11). Instead, in approximately one-third of patients with OSA (8), respiratory events are terminated early because of a low respiratory arousal threshold (ArTH), preventing the opportunity for ventilatory drive to build up and restore pharyngeal patency during sleep.…”
mentioning
confidence: 99%